Isolation and Transformation of Tefrosin From The Seed of Tephrosia Vogelii With SelectfluorTM - Yulvia, Ana; Hermawati, Elvira; Danova, Ade; Oktavianawati, Ika; Reza, Muhammad (Indonesian Chimica Letters, 2024)
In this study, tefrosin (1), a known phenolic compound, was successfully isolated and identified from the seed extract of Tephrosia vogelii. The structure of this compound was determined based on 1D and 2D NMR spectroscopy. Furthermore, the isolated compound was transformed using 0.5 equivalent of selectfluor™ in acetonitrile solvent at 100 oC for 3 hours. The reaction product, namely dehydrotephrosine (2), is new reaction product from selectfluor™ reagent as a catalyst in tertiary alcohol dehydration in aromatic group. This finding highlights the effectiveness of selectfluor™ as a catalyst in dehydration reactions, demonstrating its potential to introduce new chemical properties to compounds. The study underscores the versatility of selectfluor™ and its ability to facilitate the generation of valuable derivatives from phenolic compounds. These results provide insights into the reactivity of tefrosin and offer a new approach for chemical transformations involving phenolic substrates.